Increased Risk of Multibacillary Leprosy among Patient with Low Plasma Vitamin D Level - Luh Made Mas Rusyati (Journal of Global Pharma Technology, 2018)
Introduction: Leprosy is an emerging transmitted disease that still prevalent enough in Indonesia. Although its treatment modalities have proved to be effective, an effective preventive measure is still needed especially to prevent the development of the severe form of Leprosy. Several studies found that Vitamin D had a significant influence on the immune system and thus could potentially alter the susceptibility to Leprosy or its manifestation. Thus, this study aimed to evaluate whether the plasma vitamin D level had a significant effect on the manifestation of Leprosy. Methods: A case-control study was conducted from July to August 2016 at Dermatology and Venerology Department of Sanglah General Hospital. The leprosy was categorized into Paucibacillary (PB) and Multibacillary (MB) while plasma vitamin D level was classified into normal/high and low. Subjects with MB were included in the case group while those with PB act as acontrol.Results:50 subjects, 25 per group, were enrolled in this study in which no significant differences were found in baseline characteristics of both groups. Bivariate analysis showed that plasma vitamin D level was significantly higher in PB than in MB (24.4272 ng/ml vs. 20.1488ng/ml). In accordance to mean difference, it revealed that low plasma vitamin D significantly increase the risk of MB type leprosy (OR: 12.667; 95% CI: 3.308-48.504). Conclusion: Low plasma vitamin D level significantly increased the risk of MB type leprosy as much as 12.667 times higher than normal.Keywords: Paucibacillary Leprosy, Multibacillary Leprosy, Plasma vitamin D level.